Planet of Doom - Marlowe, Stephen, 1928-2008; Terry, W. E., 1921-1992 (Salt Lake City, UT : Project Gutenberg, 2021)
"Planet of Doom" by Stephen Marlowe is a science fiction novel written in the mid-20th century. The story revolves around the impending crisis on the planet Mandmoora, where a sun-worshipping population faces certain death as their sun is about to go nova. The book explores themes of faith, survival, and the determination of a galactic reporter, Jane Crowley, who embarks on a perilous journey to document the last moments of those who refuse to evacuate. In the narrative, Jane Crowley finds herself at the center of a dramatic situation as tensions rise between the evacuation efforts led by the military and the devoted Mandmooran sun-worshippers. Against orders, she sneaks to the island of the die-hards with the help of her ally Sid Masters, hoping to capture their final moments. As the nova draws closer, the conflict escalates, leading to a confrontation that shifts from one of destruction to as a fight for survival. Ultimately, Jane's compassion and quick thinking save the life of the Mandmooran chief's son and inspire the community to abandon their fanatical beliefs, resulting in the successful evacuation of the planet just in time, illustrating that steadfastness in faith can yield both destruction and hope. (This is an automatically generated summary.)
Release date is 2021-11-14
Greg Weeks, Mary Meehan and the Online Distributed Proofreading Team at http://www.pgdp.net
Keywords: Science fiction; Short stories; Human-alien encounters -- Fiction; Life on other planets -- Fiction; Journalists -- Fiction